PENGARUH TEKNIK MARMET TERHADAP KELANCARAN PENGELUARAN AIR SUSU IBU PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS KOTO BARU - Evin Noviana Sari; Novia Dwijayanti; Ulfa Annisa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Smooth milk discharge is very important for the health and development of the baby. The purpose of this study is to determine the effect of the marmet technique on the smooth release of breast milk in postpartum mothers in the working area of the Koto Baru Health Center. This study uses a quantitative approach method with a pre-experiment design with a research design using a one group pretest-posttest design. The population of this study is all postpartum mothers in the working area of the Koto Health Center as many as 44 people. The sample in this study is 10 people. The sampling technique uses Purposive Sampling. The results of the research on the smooth production of breast milk before the marmet technique was carried out were not smooth for 10 partum post mothers (100%). And after the marmet technique was carried out, as many as 8 postpartum mothers (80%). The analysis of the statistical test of this study using the Wilcoxon test obtained a p value of 0.007 (α 0.05), so that it can be concluded that H0 is rejected, meaning that there is an influence of the marmet technique on the smooth release of breast milk in postpartum mothers in the working area of the new Koto Health Center, Dharmasraya Regency in 2025. It is recommended that postpartum mothers can increase their knowledge and experience in an effort to increase breast milk production so that mothers can provide optimal breastfeeding. Keywords: Smooth Breastfeeding, Postpartum, Marmet Technique